Augustine and Social Justice. - Delgado, Teresa (Augustine in Conversation: Tradition and Innovation., 2015)
This volume examines some of the most contentious social justice issues present in the corpus of Augustine's writings. Whether one is concerned with human trafficking and the contemporary slave trade, the global economy, or endless wars, these essays further the conversation on social justice as informed by the writings of Augustine of Hippo.